Transformasi Digital: Perbezaan Amalan dan Jangkaan untuk Faktor Kejayaan Kritikal (FKK) Industri 4.0 - Ahmad @ Mohamad, Md Fauzi; Abdul Rahman, Nor Aida; Ahmad Nur Aizat Ahmad,; Abdul Latip, Hamrila (Research in Management of Technology and Business, 2022)
The development of the Industrial Revolution 4.0 has a direct impact on various fields including the field of manufacturing such as cyber physical systems, cloud computing, Internet of things (IoT) and smart manufacturing. There are several issues related to the performance of manufacturing companies such as low productivity, low value of labor wages and production of product quality that does not meet standards. The objectives of this research are to study the level of Industry 4.0 Critical Success Factors (CSFs) in manufacturing companies and to examine the differences of Industry 4.0 FKK in terms of practices and expectations. This research has used quantitative methods and random sampling techniques by using a survey questionnaire that was answered by a total of 104 manufacturing companies. The findings showed that overall level is CSFs and performance is above 5.50. There were no significant differences between expectations and practices except for data governance. The benefit of this study is to know the CSFs Industry 4.0 which plays an important role in influencing the performance of manufacturing companies.